Genetic Analysis of 28 Chinese Families With Tyrosinase-Positive Oculocutaneous Albinism - Ma, Linya; Zhu, Jianjian; Wang, Jing; Huang, Yazhou; Zhang, Jibo; Wang, Chao; Zhou, Yuan; Peng, Dan (Frontiers in Genetics, 2021)
Background: Tyrosinase-positive oculocutaneous albinism (OCA, type II, OCA2) is an autosomal recessive genetic disease in which the biosynthesis of melanin decreases in the skin, hair, and eyes. OCA2 is caused by mutations in OCA2. The gene product plays a role in regulating the pH of melanosomes. Up to now, hundreds of OCA2 mutations have been reported and novel variants are still being discovered. Methods: In this study, we reviewed the records of patients who had conducted albinism genetic testing, and then analyzed the clinical and genetic information of 28 patients who had been diagnosed as OCA2. Results: In this study, we reported 31 variants screened from 28 Chinese OCA2 families, and characterized the detailed molecular and clinical presentations. There were 12 novel variants among all detected variants, including 3 missense variants: p.G393V, p.T482A and p.R720P. One potential cluster of missense variants was implicated indicating the important roles of the underlying domains in OCA2 pathogenesis. Conclusion: Our results were beneficial for diagnosis and precision clinical management for OCA2-related disorder, and this study expanded the mutation spectrum of oculocutaneous albinism.